Avaliação da Qualidade da Água do rio Pitimbu - Sena, Diogenes Santos de (2008)
The Pitimbu River Basin is concern reason, therefore this is one of the mains freshwater sources for the Natal city supplying. The Pitimbu waters river flow into Jiqui pond, as the main supplier of this, that supplies 16% of Natal population and there is a bigger importance despite the supplying of a parcel of Natal city made joining underground waters with the water proceeding from the Jiqui pond, being used for dilution waters of contaminated wells with nitrate. Even with the importance of the Pitimbu, there is a strong pressure of occupation of its edge according to a critical urban growth, becoming the situation worse and increasing the necessity of management of the use and occupation of the ground and keeping the control of the prompt pollution, as punctual as diffuse. There are many studies about Pitimbu River Basin, however they summarize themselves to some months or even in a few years. This work, that gathers these information, increasing the amplitude and making possible an evaluation of the attitude of the water in a period extended for an evaluation of values of variable quality of water referring to the standards, that usually happens about the variable frequency distribution, central tendency and measures of dispersion, as the coefficient of variation, coefficient of skewness and the coefficient of determination of certain variable on another one. This work to evaluates the quality conditions of the Pitimbu river waters by analyzing thirty five (35) variables Physical, chemical and biological in eight (8) points of water course since 1993 to 2007. Given this situation, all knowledge about the waters quality conditions obtained in this work, is a strong subsidy for management of use and ground occupation, considering the river basin as territorial unit of management, and as the water is public good domain, being a priority human use, It is necessary to guarantee to current and the future generations available water resources in appropriate standards of quality as the established standard and identifying possible reasons of pollution through statistics analysis